Pentahelix Approach in The Implementation of Disaster Resilient Village (Destana) Sumber Village Magelang Regency - Julio Adi Bhaskara; Titin Purwaningsih (Department of Public Administration, Muhammadiyah University of Makassar, 2023)
This study aims to analyse the implementation of the Disaster Resilient Village (Destana) program in Sumber Village, Magelang Regency, and the role of the actors involved in the pentahelix collaboration concept in the implementation process. This research is qualitative descriptive research. The research location was in Magelang Regency, especially in Sumber Village. Data collection techniques using observation, documentation, and in-depth interviews with informants using purposive sampling. The research found that five actors in the Pentahelix concept, namely academics, business, community, government, and media, have roles in implementing the Destana program. Government, community, and academics are actors who have a significant role in implementing Destana. the business and media sectors are less visible because they are only seen when a disaster has occurred. The synergy in Destana in Sumber Village was seen when implementing the Inclusion-Based Disaster Simulation, where academics, government, community, and media actors participated. The Destana Sumber Village program still has not seen synergy from five actors due to the lack of roles of business actors in disaster risk reduction activities. The recommendation is to include Corporate Social Responsibility (CSR) in the implementation of Destana.